Granuloma Faciale - Sarkar Rashmi; Kanwar Amrinder J (Wolters Kluwer Medknow Publications, 2002)
Granuloma faciale is an uncommon dermatosis of unknown aetiology, usually characterized by a solitary reddish-brown plaque or a nodule on the face. We report an unusual case of granuloma facial where the lesions were multiple and they responded to intralesional triamcinolone injections.